Slačenje literarne zgodovine - Zavrl, Andrej (Primerjalna književnost, 2008)
The area that seems to have been quite persistently controlled up to the present day is that of sexual non-normativity. A clear expression of the still-present unspeakability of same-sex desire - as an instance of such non-normativity - is seen in the different ways of censoring literature representing same-sex desire.
Keywords: literatura in cenzura; homoseksualnost; homosexuality; gay literature; gejevska književnost; lezbična književnost; slovenska literarna kritika